(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To analyze the budgetary impact and the increase in costs of the incorporation of special surfaces for pressure management to prevent pressure injuries in bedridden elderly patients. Method: Budget impact analysis, following the recommendations of the budget impact analysis methodological guideline. Two possible scenarios were out lined. In the first (alternative) scenario, the elderly receives a prevention strategy that includes the use of a viscoelastic mattress as a pressure distribution surface and a change in position with a minimum interval of 2 hours. In the second scenario (reference), the elderly receives a prevention strategy that only includes a change in position with a minimum interval of 2 hours. All costs were estimated using the macro costing technique. Results: The results of the analysis of the budget impact speak in disfavor, therefore, contrary to the eventual incorporation of the viscoelastic mattress as a complementary strategy to the systematic change of decubitus, of at least every 2 hours as a measure to prevent pressure injuries. Conclusion: The use of high technologies will not always be the differential for the best clinical outcome of the patient and it can result in more cost to the system.